The Influence of Imagery on The Field Tennis Serve Skills - Trinovandhi Setyawan; Paulus Rah Adi Pawitra; Mushofi, Yuskhil; Ernata, Yusvidha (Universitas PGRI Palembang, 2024)
Basic technical skills in the game of field tennis are still often found several obstacles, one of which is the basic technique of serving. Many students who take field tennis courses still experience errors when serving. They tend not to feel confident and hesitate when serving, so an approach is needed to overcome the problem, one of which is using imagery. The methodology used is quasi experiment, where the implementation does not use a control class. The research subjects were PJKR students of Insan Budi Utomo University who were taking field tennis courses as many as 40 students. From the research that has been carried out, it has been obtained in the form of t-test results and t-count results where it is found to be greater than the t-table, 2.86> 2.262, therefore there is a difference in the increase from pre-test to post-test. Where in the pre-test average result is 8.4, while the post-test average result after imagery training is 15.5. In addition, imagery training has an influence of around 84.52% on the results of tennis serving skills in PJKR students at Insan Budi Utomo University